Perbedaan Hasil Belajar Siswa Kelas X Jurusan Multimedia pada Pembelajaran Meaningful Instructional Design (MID) dan Discovery Learning pada Mata Pelajaran Komputer dan Jaringan Dasar di SMK Negeri 2 Singosari Malang - Salma Berliana Putri; Admaja Dwi Herlambang; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Understanding the concept during learning activities is very important, because it will affect the acceptance of the next material and learning outcomes that have an impact on skills. Student learning outcomes that are less than optimal also occur in class X students at SMKN 2 Singosari Malang in Computer and Basic Network subjects. The cause of the less than optimal learning outcomes is because students are burdened with subjects with conceptual material. To maximize the understanding of the material, an appropriate learning model is needed to improve the understanding of concepts in students. This study aims to determine the comparison of student learning outcomes before and after using the Meaningful Instructional Design Learning Model and the Discovery Learning Model and to determine whether there is an increase in grades after using the two learning models. This research is a quantitative research with the type of experimental method with a sample of 50 students. The data obtained and has been processed can be concluded that the learning outcomes of students in the Computer and Basic Network subjects, namely those obtained from the Lavene's Test value are not significant, because p = 0.632 > 0.05 which means the variance in both groups is the same. Next, look at the value of Sig.(2-tailed) in the first line, which is 0.856 > 0.05, which means that there is no significant difference in learning outcomes between classes with the Meaningful Instructional Design Learning Model and the Discovery Learning Model.